The impact of immune-related adverse events on the outcome of advanced gastric cancer patients with immune checkpoint inhibitor treatment - Zhang, Tianhang; Lv, Haitao; Li, Jiasong; Zhang, Shasha; Zhang, Jingjing; Wang, Siqi; Wang, Yingnan; Guo, Zhanjun (Frontiers in Immunology, 2024)
BackgroundThe occurrence of immune-related adverse events (irAEs) seemed to be associated with better outcomes in advanced gastric cancer (AGC) patients. However, research focusing on the impact of the single-organ irAE (uni-irAE) or multi-organ irAEs (multi-irAEs) on the AGC outcome is relatively limited. In this study, we investigated individually the impact of the different irAEs on AGC survival as well as the co-occurrence patterns of multi-irAEs.MethodsThe uni-irAE, multi-irAEs, and non-irAE were identified based on National Comprehensive Cancer Network (NCCN) guidelines. ICI efficacy for the disease control rate (DCR) and the objective response rate (ORR) was assessed based on the Response Evaluation Criteria in Solid Tumors (RECIST) Version 1.1. The association for the irAEs with progression-free survival (PFS) or overall survival (OS) was analyzed using the Kaplan–Meier method and Cox regression model. We also performed pairwise correlation analysis to identify co-occurrence patterns of multi-organ irAEs.ResultsA total of 288 patients including 175 non-irAE, 73 uni-irAE, and 40 multi-irAE patients were evaluated for their association with AGC outcome. The irAEs patients displayed higher DCR (78.8% vs. 67.4%, p=0.037) when compared with those of non-irAE patients, and both uni-irAE patients (82.2% vs. 67.4%, p=0.019) and multi-irAE patients (72.5% vs. 67.4%, p=0.534) showed higher DCR than that of non-irAE patients. The multivariate analyses revealed that multi-irAEs was an independent risk factor for PFS (hazard ratio [HR] of 0.63, 95% confidence interval [CI] 0.41~0.96, p=0.031) and OS (HR 0.47, 95% CI 0.29~0.76, p=0.002), whereas the survival association for uni-irAE was not obtained. The analysis of the co-occurrence patterns for multi-irAEs revealed that the thyroid, adrenal gland, heart, skin, and lung irAEs exhibited a high risk of co-occurrence of multi-irAEs. The multivariate Cox regression analysis for organ-specific irAEs revealed that patients experiencing thyroid, adrenal gland, and skin irAEs had favorable survival outcomes compared with those without these irAEs.ConclusionMulti-irAEs and some organ-specific irAEs can be used as predictive indicators for ICI treatment efficacy in AGC patients. The thyroid, adrenal gland, heart, skin, and lung irAEs are often accompanied by multi-irAE occurrence.